Synthesis of fatliquor from waste bovine fat for use in small scale leather industry - Nyamunda, B. C.; Moyo, Mambo; Chigondo, Fidelis (NISCAIR, 2016)
In this study, fatliquor has been synthesized from waste bovine fat for its use in small scale leather industry. The physico-chemical properties of bovine fat are determined before sulphation with sulphuric acid followed by the subsequently neutralization with ammonia to produce the fatliquor. The fatliquor is subjected to chemical and physical analyses. The degree of sulphation is found to be 90% and the surface active groups of the fatliquor are observed in anionic form. The fatliquor has been applied onto light leather and physical tests are carried out on the fixed leathers. The results of the physical tests on fixed leather conform to the standard leather specifications. It is observed that the synthesized fatliquor could be used as an alternative in leather fixation.